2014
DOI: 10.1016/j.biomaterials.2014.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiogenic factors and 3D-microenvironments on vascularization within sandwich cultures

Abstract: The in vitro fabrication of vascularized tissue is a key challenge in tissue engineering, but little is known about the mechanisms of blood-capillary formation. Here we investigated the mechanisms of in vitro vascularization using precisely-controlled 3D-microenvironments constructed by a sandwich culture using the cell-accumulation technique. 3D-microenvironments controlled at the single layer level showed that sandwich culture between more than 3 fibroblast-layers induced tubule formation. Moreover, the secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 34 publications
2
81
1
Order By: Relevance
“…Endothelium grown in 3D conditions by the use of matrigel or hydrogel substrates displays the typical ability to form interconnected tubules and its gene expression and cell signaling are clearly different from the monolayer cultures (Blobel, 2010;Engelse, Laurens, Verloop, Koolwijk, & van Hinsbergh, 2008;Hofmann et al, 2008;X. Ma et al, 2013;Nishiguchi, Matsusaki, Asano, Shimoda, & Akashi, 2014;Pedersen et al, 2013b).…”
Section: Critical Concernsmentioning
confidence: 99%
“…Endothelium grown in 3D conditions by the use of matrigel or hydrogel substrates displays the typical ability to form interconnected tubules and its gene expression and cell signaling are clearly different from the monolayer cultures (Blobel, 2010;Engelse, Laurens, Verloop, Koolwijk, & van Hinsbergh, 2008;Hofmann et al, 2008;X. Ma et al, 2013;Nishiguchi, Matsusaki, Asano, Shimoda, & Akashi, 2014;Pedersen et al, 2013b).…”
Section: Critical Concernsmentioning
confidence: 99%
“…Early osteoblastic and 24 endothelial differentiations were observed and cell pro- 25 liferation was increased after 7 days of culture. In 3D, cell 26 migration was observed between layers of LBL constructs, 27 as well as an osteoblastic differentiation. These results 28 indicate that LBL assembly of PLA layers could be suitable 29 …”
Section: Tissue Engineering Constructs and Cell Substratesmentioning
confidence: 99%
“…We observed that both the expression of angiogenic factors from surrounding NHDFs and effect of 3D microenvironments affected the vascularization by sandwich cultures. 83 Therefore, such blood capillaries with a lumen have enormous potential for drug permeability testing or tumor angiogenesis and metastasis assays.…”
Section: Cell Accumulation Technique For Vascularized 3d Tissue Constmentioning
confidence: 99%